2021
DOI: 10.1002/adma.202106149
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering with Mechanically Induced Solid‐Fluid Transitions

Abstract: Epithelia are contiguous sheets of cells that stabilize the shape of internal organs and support their structure by covering their surfaces. They acquire diverse morphological forms appropriate for their specific functions during embryonic development, such as the kidney tubules and the complex branching structures found in the lung. The maintenance of epithelial morphogenesis and homeostasis is controlled by their remarkable mechanics—epithelia can become elastic, plastic, and viscous by actively remodeling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…[ 4 ] Our study suggested that after TGF‐ β stimulation, cells upregulated the tension around the periphery through sensing the confined geometry of microtissue, resulting in a “solid”‐like state ( Figure ), in agreement with a recent report about mechanically induced solid‐fluid transitions of epithelial microtissues. [ 45 ] The actomyosin coordination and contractility between neighboring cells at the periphery of “solid” microtissue, resisted external disruptive forces and maintained tissue coherence, thus preventing cells from invading into the surrounding matrix.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] Our study suggested that after TGF‐ β stimulation, cells upregulated the tension around the periphery through sensing the confined geometry of microtissue, resulting in a “solid”‐like state ( Figure ), in agreement with a recent report about mechanically induced solid‐fluid transitions of epithelial microtissues. [ 45 ] The actomyosin coordination and contractility between neighboring cells at the periphery of “solid” microtissue, resisted external disruptive forces and maintained tissue coherence, thus preventing cells from invading into the surrounding matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The robot successfully dissected the targeted tissue using the same image processing functions described in Case Study 1 (see Video 4). Our platform and approach could also be applied to other model organisms, including amphibians, chick, and mouse embryos as well as organoids and other tissue culture models [31], providing endless experimental opportunities for biomedical research.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogel and cells were housed in a microfluidic device that controlled pressure and flow in the vessel, and the authors were able to examine the role of hydrogel poroelastic properties in regulating the dynamics of the vessel. Another exciting study demonstrated the potential of epithelial tissues to form shape-programmable materials by using a collagen scaffold (Mailand et al, 2022).…”
Section: Controlling Geometry and Physical Forcesmentioning
confidence: 99%